Garuga pinnata attenuates oxidative stress and liver damage in chemically induced hepatotoxicity in rats. Issue 1 (1st January 2021) - Chavan, Sandeep; Dias, Remeth; Magdum, Chandrakant
ABSTRACT: Aim: The aim of the current research work was to isolate, characterize and evaluate the hepatoprotective activity of Garuga pinnata leaves in both acute and chronic hepatic disorder. Materials and methods: The ethanolic extract of the leaves was evaluated for phytochemical screening, acute oral toxicity studies and In-vivo hepatoprotective activity. Hepatotoxicity was induced by administration of paracetamol, thioacetamide and ethanol in albino wistar rats. Serum and tissue biochemical parameters were estimated. Histopathological studies were performed using hematoxylin and eosin staining. The active principle from plant was isolated using column chromatography and identified by UV, FTIR, NMR, and GC-MS studies. Results: Animal groups treated with hepatotoxicant showed marked alteration in serum and tissue biochemical parameters. However, pretreatment with ethanolic extract significantly restored the biochemical parameters. Garuga pinnata leaves extract showed the dose-dependant hepatoprotective effect. Histopathology of the groups treated with leaves extract showed normal hepatic architecture confirming hepatoprotective activity. Analytical techniques including UV, FTIR, NMR and mass confirmed the presence of rutin flavonoids and hence the hepatoprotective activity was attributed to chemical compound rutin. Conclusion: Ethanolic leaves extracts can serve as promising herbal medicine for the treatment of both acute and chronic hepatotoxicity due to the presence of flavonoids rutin. Graphical abstract: uf0001